1993
DOI: 10.1007/bf01991142
|View full text |Cite
|
Sign up to set email alerts
|

Expression of mRNA for interleukin 6 by cells infiltrating epiretinal membranes in proliferative vitreoretinopathy

Abstract: We have investigated the expression of mRNA for interleukin 6 (IL-6) in cells infiltrating 12 epiretinal membranes, and the presence of biologically active IL-6 in vitreous humour available from five corresponding eyes. The results showed that nine of the 12 membranes (75%) contained cells expressing mRNA for this cytokine. Although in two of the specimens pigmented cells were identified as some of the cells expressing mRNA for IL-6, we did not identify the nature of IL-6 mRNA-producing cells infiltrating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…Increasing evidence suggests that inflammatory cytokines such as IL-1, TNF, IL-6 and TGF-Pi are involved in the pathogenic process of PVR and PDR. These cytokines have been identified in the epiretinal membrane or the vitreous of patients with PVR or PDR [1][2][3][4][5]. In vitro studies have shown that retinal pigment epithelial cells can synthesize mRNA or proteins for these cyto kines in response to inflammatory stimuli [9,[17][18][19][20][21][22], Our results suggest that retinal isch emia causes up-regulation of gene expression for these cytokines in retinal ischemic dis eases.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Increasing evidence suggests that inflammatory cytokines such as IL-1, TNF, IL-6 and TGF-Pi are involved in the pathogenic process of PVR and PDR. These cytokines have been identified in the epiretinal membrane or the vitreous of patients with PVR or PDR [1][2][3][4][5]. In vitro studies have shown that retinal pigment epithelial cells can synthesize mRNA or proteins for these cyto kines in response to inflammatory stimuli [9,[17][18][19][20][21][22], Our results suggest that retinal isch emia causes up-regulation of gene expression for these cytokines in retinal ischemic dis eases.…”
Section: Discussionmentioning
confidence: 50%
“…Inflammatory cytokines have been implicated in the pathogenesis of various retinal diseases such as proliferative vitreoretinopathy (PVR) and proliferative diabetic retinopathy (PDR) [1][2][3][4][5]. Recently we showed that transient reti nal ischemia up-regulated interleukin-1 (IL-1) gene expression in rat retina [6], It is, there fore, possible that retinal ischemia causes upregulation of other inflammatory cytokines such as tumor necrosis factor (TNF) in the retina.…”
Section: Introductionmentioning
confidence: 99%
“…Cells with IL-6 mRNA expression have been found in PVR epiretinal membranes 20 and previous work has also have shown that the vitreous levels of IL-6 are significantly raised in vitreous samples obtained from patients with PVR. 18 19 21 The consistent finding of raised IL-6 levels is evidence for its role in the marked blood-retinal barrier breakdown seen in PVR.…”
Section: Discussionmentioning
confidence: 84%
“…The large amounts of these cytokines produced by choroidal melanomas could contribute to the inflammation process of exudative retinal detachment. The detectable levels of these cytokines may indicate a cytokine-mediated pathway of inflammation involved in the pathogenesis of PVR, too [23]. Furthermore, the large amounts of IL-8 detectable in the supernatants of choroidal melanoma correlate with the findings in human cutaneous melanomas [5].…”
Section: Discussionmentioning
confidence: 75%